2015
DOI: 10.2174/0929867322666150812145035
|View full text |Cite
|
Sign up to set email alerts
|

Role of Serum and Glucocorticoid-Inducible Kinase (SGK)-1 in Senescence: A Novel Molecular Target Against Age-Related Diseases

Abstract: Senescence is a phenomenon characterized by a progressive decline of body homeostasis. Premature senescence acts when the cellular system is not able to adequately respond to noxious stimuli by synthesis of stressor molecules. Among those, serum-and-glucocorticoidinducible kinase-1 (SGK-1) dramatically increases under typical physiopathological conditions, such as glucocorticoid or mineralcorticoids exposure, inflammation, hyperglycemia, and ischemia. SGK-1 has been implicated in mechanism regulating oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…Furthermore, physiological studies have demonstrated the involvement of SGK1 in regulating tissue inflammation with known contribution to hypertension pathophysiology. 19,20 In aggregate, these data provide strong evidence for a role of SGK1 in hypertension development.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Furthermore, physiological studies have demonstrated the involvement of SGK1 in regulating tissue inflammation with known contribution to hypertension pathophysiology. 19,20 In aggregate, these data provide strong evidence for a role of SGK1 in hypertension development.…”
Section: Discussionmentioning
confidence: 63%
“…17,18 Recent in vitro and in vivo studies showed that SGK1 can promote tissue inflammation and cell senescence, providing a new insight into BP regulation. 19,20 Similar to SGK1, SGK2, and SGK3 can also influence Na+/H+ exchanger 3 activity and potentially regulate Na+ transport. 8 SGK's biological relevance along with evidence from in vitro and in vivo studies make the SGK genes important candidates for genetic study of BP phenotypes.…”
mentioning
confidence: 99%
“…mRNA levels of CNTF (C), SESN3 (D), and iNOS (E) in the brain homogenates from mice treated with BN201 for 5 days (black line) and the corresponding BN201 CNS levels (in red). *p < 0.05 day 5, 10, or 15 with respect to day 0 of the same treatment group, ANOVA test Previous studies have shown neurotrophic effects of SGK1, including the induction of neuronal hypertrophy, protection from neuron death and axonal degeneration, and axonal regeneration [43,52,53]. Moreover, MDK also displays prosurvival neuronal effects and protects myelin-forming cells [54,55].…”
Section: Discussionmentioning
confidence: 96%
“…Analysis of proteinprotein interaction databases pointed to the activation of the midkine-nucleolin-PTGES3 axis, like the SGK pathway, which participates in the trophic factor pathway (PI3K-AKT pathway) and protects neurons against damage (e.g., kainic acid-induced seizures, ischemia, or amyloid beta toxicity) [41]. SGKs are expressed strongly in all types of neurons and it is considered to be a stress sensor [42], promoting the expression of antioxidant enzymes and the modulation of ion channels [43], as well as participating in trophic factor pathways (e.g., insulin growth factor 1 (IGF-1) receptor pathway), promoting neuronal survival. Indeed, MDK also activates the IGF-1 pathway.…”
Section: Bn201 Activates Neuronal Survival Pathwaysmentioning
confidence: 99%
“…In line with a previous report of a protective effect of endogenous catalase activity in fatty liver [ 42 ], a further novel finding of our study was the observation that half of the genes that center around SREBP-1 and differ in regulation according to the ability of SREBP-1a to be phosphorylated are correlated with peroxisomal catalase activity. These included genes like CWF19L1, which was previously shown to act in fatty liver and metabolic diseases [ 43 , 44 , 45 , 46 ]. Furthermore Lcn2 (lipocalin-2) correlated to catalase activity dependent on SREBP-1a phosphorylation.…”
Section: Discussionmentioning
confidence: 99%